Systematic review of the evidence for sustained efficacy of dietary interventions for reducing appetite or energy intake - Halford, Jason C.G.; Masic, Una; Marseaux, Cyril F.M.; Jones, Andrew J.; Lluch, Anne; Marciani, Luca; Mars, Monica; Vinoy, Sophie; Westerterp-Plantenga, Margriet; Mela, David J. (Wiley, 2018)
We assessed evidence for changes in efficacy of food-based interventions aimed at reducing appetite or energy intake (EI), and whether this could be used to provide guidance on trial design. A systematic search identified randomized controlled trials testing sustained efficacy of diets, foods, supplements or food ingredients on appetite and/or EI. Trials had to include sufficient exposure duration (≥3 days) with appetite and/or EI measured after both acute and repeated exposures. Twenty-six trials met the inclusion criteria and reported data allowing for assessment of the acute and chronic effects of interventions. Most (21/26) measured appetite outcomes and over half (14/26) had objective measures of EI. A significant acute effect of the intervention was retained in 10 of 12 trials for appetite outcomes, and six of nine studies for EI. Initial effects were most likely retained where these were more robust and studies adequately powered. Where the initial, acute effect was not statistically significant, a significant effect was later observed in only two of nine studies for appetite and none of five studies for EI. Maintenance of intervention effects on appetite or EI needs to be confirmed, but seem likely where acute effects are robust and replicable in adequately powered studies.